Neurosensory Evaluation of the Inferior Alveolar Nerve: Must Know in Dental Office - Kulkarni, Vishal; Sahoo, N. K. (Neurosensory Evaluation of the Inferior Alveolar Nerve: Must Know in Dental Office, 2021)
Mandible receives maximum impact during trauma making it the most widely recognised form of fracture after its sustenance. Owing to varied information worldwide exact data acquisition is hard. Nevertheless, primary aetiology seems to be vehicular mishaps (43%) trailed by assaults, occupational, falls and sports related. More slender anatomy with biomechanically altering musculature alters fracture propogation mechanism. Encasement of inferior alveolar nerve (IAN) may get infringed and lead to loss of sensation in chin and lip area. Reports indicate a IAN deficit of 5.7%-58.5% pre-treatment and 04%-91.3% post-osteosynthesis. There are some gold standard testing algorithms (Zuniga and Essick; modified British medical research scale) later modified by Mackinnon-Dalon for Trigeminal nerves. These are seldom used in practice. Be that as it may, a robust modification for routine examination is needed. The following texts have tried to envisage the use of local equipments and materials that are available easily in our dental office and can be utilized for neurosensory evaluation. This proves economical, speedy yet efficient in documentation of neurosensory stauts of IAN.